Measuring Water Parameters Around Pamayangsari Port in Tasikmalaya - Rostika, Rita; Zallesa, Sheila (International Journal Labs, 2023)
Pamayangsari Beach provides facilities and infrastructure supporting fishermen's activities in Pamayangsari, such as docks, TPI, boats and fishing gear. Pamayangsari Port or pier is a fishing port that is quite actively operating. Fish loading and unloading activities at ports can also produce waste, both liquid waste and solid waste. This research activity was carried out to assess how much impact might arise on the biophysical environment around Pamayangsari Port, especially for its water quality parameters. The method used in this activity is a survey method with direct collection of field data where the water quality parameters measured include temperature, salinity, pH, DO, Brightness and Substrate. Based on the results of measuring water parameters, namely temperature, salinity, DO, pH, Brightness and Substrate, the waters around the port of Pamayangsari are still in the category of water quality standards of the Ministry of Environment and Forestry where the value of pamayangsari waters ranges from 31-34 ppt, temperature values are in the range of values of 28.5 – 29.1 °C, pH values are in the range of 9.72 to 9.97, DO values are 7.9-9.2 ml / g. for the brightness level of the waters around the port of pamayangsari is in the range of values 0.2 – 1.3 meters and the substrate type is dominated by sandy substrate.